Peran dan Fungsi Covernote Dalam Pelaksanaan Pencairan Kredit Oleh Bank - Oktarini, Anak Agung Ayu Diah; Agung Dharma Kusuma, Anak Agung Gede (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 9 No 4 (2020), 2020)
Covernote issued by the Notary for the acceleration of credit disbursement. The problem is the legal position of the covernote issued by the Notary in the disbursement process carried out by the Bank and how the credit disbursement process by the Bank is based on the covernote. The research objective is to find out and explain the concept of the legal position of the covernote in terms of implementing credit disbursements by. This study uses an empirical juridical research method, with a prescriptive analytical approach. The discussion obtained is the legal position of the covernote, namely only in the process of credit realization carried out by the Bank, the legal force of the covernote is not binding on the covernote, only a certificate in process, and not a single article states or interprets the notary's authority to issue a covernote, in the process of credit disbursement The problem that occurs is that the HT certificate settlement has not been completed while the credit has been disbursed based on the covernote, and another problem is the occurrence of congestion in credit payments which causes the debtor to default and the bank experiences a loss. Covernote dikeluarkan oleh Notaris untuk percepatan pencairan kredit. Permasalahanya adalah kedudukan hukum daripada covernote yang diterbitkan oleh Notaris di dalam proses pencairan yang dilakukan oleh Bank serta bagaimana proses pencairan kredit oleh Bank berdasarkan covernote. Tujuan penelitian mengetahui dan menjelaskan konsep dari kedudukan hokum covernote dalam hal pelaksaan pencairan kredit oleh. Penelitian ini menggunakan metode penelitian yuridis empiris, dengan melakukan pendekatan preskriptif analitis. pembahasan yang diperoleh adalah kedudukan hukum covernote yakni hanya dalam proses realisasi kredit yang dilakukan oleh Bank, kekuatan hukum covernote tidaklah bersifat mengikat melainkan covernote hanya sebatas surat keterangan yang masih dalam proses, dan tidak ada pasal yang menyatakan atau menafsirkan kewenangan dari Notaris untuk menerbitkan covernote, dalam proses pencairan kredit masalah yang terjadi adalah penyelesaian sertifikat HT tak kunjung selesai dalam keadaan kredit telah dicairan berdasarkan covernote, dan permasalahan yang lain adalah terjadinya kemacetan dalam pembayaran kredit sehingga menyebabkan debitur melakukan wanprestasi dan pihak bank mengalami kerugian.